Magnetic Field–Suppressed Lithium Dendrite Growth for Stable Lithium‐Metal Batteries - Shen, Kang; Wang, Zeng; Bi, Xuanxuan; Ying, Yao; Zhang, Duo; Jin, Chengbin; Hou, Guangya; Cao, Huazhen; Wu, Liankui; Zheng, Guoqu; Tang, Yiping; Tao, Xinyong; et al. (Advanced energy materials, 2019)
Lithium metal is the most attractive anode material due to its extremely high specific capacity, minimum potential, and low density. However, uncontrollable growth of lithium dendrite results in severe safety and cycling stability concerns, which hinders the application in next generation secondary batteries. In this paper, a new and facile method imposing a magnetic field to lithium metal anodes is proposed. That is, the lithium ions suffering Lorentz force due to the electromagnetic fields are put into spiral motion causing magnetohydrodynamics (MHD) effect. This MHD effect can effectively promote mass transfer and uniform distribution of lithium ions to suppress the dendrite growth as well as obtain uniform and compact lithium deposition. The results show that the lithium metal electrodes within the magnetic field exhibit excellent cycling and rate performance in a symmetrical battery. Additionally, full batteries using limited lithium metal as anodes and commercial LiFePO4 as cathodes show improved performance within the magnetic field. In summary, a new and facile strategy of suppressing lithium dendrites using the MHD effect by imposing a magnetic field is proposed, which may be generalized to other advanced alkali metal batteries. An novel external strategy of imposing a magnetic field to lithium metal anodes is presented. The generated Lorentz force due to the electromagnetic fields is used to promote mass transfer and uniform distribution of lithium ions. This magnetohydrodynamics effect can effectively suppress the dendrite growth as well as obtain uniform and compact lithium deposition with the remarkable performance.